If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + -5x = -28 Solving 17 + -5x = -28 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + -5x = -28 + -17 Combine like terms: 17 + -17 = 0 0 + -5x = -28 + -17 -5x = -28 + -17 Combine like terms: -28 + -17 = -45 -5x = -45 Divide each side by '-5'. x = 9 Simplifying x = 9
| 5/8y-1/4=1/3 | | 3x-2x+5=-3 | | x^2+4*k*x-k+1=0 | | 5[2y+7]=20 | | y2/y6 | | 3[y+4]=24 | | 8x^2-150x+670=0 | | 2x-11=-2 | | X-22=1/3x | | 15y^3/3y | | 5p+12=17 | | h/2-1=3 | | -20h+h^2=-25 | | 3sin(x)+3sin(3x)=0 | | 2m-1=4m-7+2 | | 10y=5x-19 | | X/7=14-x/25 | | 1=7y-8 | | f(x)=108 | | 9*(7+x)= | | -5s+14s=3s | | 8x+6y=268 | | -5S-14=3s | | -5-14s=3s | | X^3-5x-66=0 | | 9b+2b-8a-3b= | | 5-14s=3s | | 36x^2-6=58 | | 3+x^5= | | (-2)^(1/2) | | 18^(1/2)/(-2)^(1/2) | | 9x^2-9(p+q)x+(2p^2+5pq+2q^2)=0 |